2014
DOI: 10.1139/cjz-2013-0205
|View full text |Cite
|
Sign up to set email alerts
|

Do nest exclosures affect the behaviour of Piping Plovers (Charadriusmelodus melodus) and their predators?

Abstract: Predators are a threat to many ground-nesting shorebirds; however, nest exclosures are a tool used by managers to reduce nest predation. Others have found that nest exclosures increase hatching success, but there has been concern that they may also increase adult mortality and nest abandonment. We examined the effects of nest exclosures on the behaviour of incubating Piping Plovers (Charadrius melodus melodus Ord, 1824) and their predators on nesting beaches in eastern Canada. Using a combination of field obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
8
2
Order By: Relevance
“…Our findings differ from those of Beaulieu et al (2014), who found that foxes lingered outside of exclosed nests for longer and visited exclosed nests more often compared to unexclosed nests. The differences in findings between our work and that of Beaulieu et al (2014) may be due to methodological differences between the 2 studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings differ from those of Beaulieu et al (2014), who found that foxes lingered outside of exclosed nests for longer and visited exclosed nests more often compared to unexclosed nests. The differences in findings between our work and that of Beaulieu et al (2014) may be due to methodological differences between the 2 studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the potential for exclosures to protect nests against predation, there are concerns over whether these conspicuous structures might attract predators to nest sites. If so, the possibilities of increased parental abandonment, predation of adults at nests, or predation of chicks immediately after hatching could negate the benefits of reduced nest predation associated with exclosure use (Neuman et al 2004, Barber et al 2010, Beaulieu et al 2014, Dinsmore et al 2014, Cohen et al 2016). In addition, the relative benefits of exclosure use may decrease if their protective power is compromised.…”
mentioning
confidence: 99%
“…successful ex situ breeding) but the ultimate goal of population enhancement or stabilisation may not be achieved. Furthermore, side-effects such as behavioural modifications, which subsequently may affect demography or site fidelity, are often not assessed (Beaulieu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…) or by attracting predators to nest sites (Beaulieu et al. , Ferreira‐Rodríguez and Pombal ). These impacts can counteract potential increases in reproductive success (Mabee and Estelle , Johnson and Oring , Pearson et al.…”
mentioning
confidence: 99%
“…However, nest cameras have rarely been used to monitor protected and unprotected nests in previous exclosure studies (Beaulieu et al. ). Some investigators have used cameras to survey potential predator communities rather than actual predators at nests (Ferreira‐Rodríguez and Pombal ), and to identify predators at artificial (Major et al.…”
mentioning
confidence: 99%